Сводный катaлог арабскоалфавитных рукописей литовских татар: коллекция Гродненского государственного музея истории религии - Мишкинене, Галина (Slavistica Vilnensis, 2011)
Galina MiškinienėThe Summary Catalogue of Lithuanian Tatar Manuscripts in Arabic Script: the Collection in Grodno Religion History MuseumOne of the main tasks in year 2007 was composition of summary catalogue of Lithuanian Tatar manuscripts in Arabic script. Recently, the manuscript collections have been supplemented by new findings coming from some Tartars families. These findings will be presented in the new summary catalogue of Lithuanian Tatar manuscripts. In this catalogue will be described collections stored in Kazan, Minsk, Grodno, Leipzig, London, Saint Petersburg, and elsewhere. One of the collections that is described in this article is stored in Grodno Religion History Museum.